(untitled) (Research, Society and Development, 2021)
During the passage of time, it is necessary for a legal system to introduce structural reforms, given the maximum effectiveness of Law. And, among the main reforms proposed to the Brazilian order, there is the tax reform, represented, above all, by the PEC 45/2019. Several points are innovative, such as the adoption of the Value Added Tax (VAT) - renamed Tax on Goods and Services (IBS) - on consumer goods, in the three federal spheres, the basis of which comes from five other taxes: Tax on Industrialized Products ( IPI), Tax on Circulation of Goods and Services (ICMS), Tax on Services (ISS), Contribution to the Financing of Social Security (Cofins) and Social Integration Program (PIS); having specific rates for each federative entity and abolition of taxes such as the Tax on Financial Operations (IOF). However, would the creation or abolition of these taxes be positive or negative for the fiscal decentralization proposed in the 1988 Charter? An unsolvable dichotomy. Despite the selective rates for the three federative entities (Union, States and Municipalities), the Reform intends to create a central body, whose character would be to inspect such rates according to the total. There is, therefore, a paradox: between one and triune. Based on such affirmative assumptions, this article will have an exploratory character, with deduction as a method and data collection extracted from documents, bibliography and data taken from administrative bodies.